A new social physic: The sociology of Gabriel Tarde and its legacy - Tonkonoff, Sergio Esteban (2013)
This article aims to present a reconstruction of Gabriel Tarde’s micro-sociology in order to highlight its current relevance. The author of the article attempts to show that its distinction lies in taking the immense diversity of small social interactions as a starting point for the analysis of both face-to-face situations and large-scale institutions and social processes. Here the social field is described as made up of multiple propagations of desires and beliefs that spread from one individual to other, taking countless directions, interfering with each other, forming networks, and escaping them in search of new connections. The author attempts to show, also, that this point of view doesn’t deny the existence of social systems but understands them as open ensembles of immanent and partial relationships of collective beliefs and desires. This is why Tarde may be considered the founder of a molecular or micro-physical sociology.